Tapping the Potential of Multimodal Non-invasive Brain Stimulation to Elucidate the Pathophysiology of Movement Disorders - Shukla, Sakshi; Thirugnanasambandam, Nivethida (Frontiers in Human Neuroscience, 2021)
This mini-review provides a detailed outline of studies that have used multimodal approaches in non-invasive brain stimulation to investigate the pathophysiology of the three common movement disorders, namely, essential tremor, Parkinson’s disease, and dystonia. Using specific search terms and filters in the PubMed® database, we finally shortlisted 27 studies in total that were relevant to this review. While two-thirds (Brittain et al., 2013) of these studies were performed on Parkinson’s disease patients, we could find only three studies that were conducted in patients with essential tremor. We clearly show that although multimodal non-invasive brain stimulation holds immense potential in unraveling the physiological mechanisms that are disrupted in movement disorders, the technical challenges and pitfalls of combining these methods may hinder their widespread application by movement disorder specialists. A multidisciplinary team with clinical and technical expertise may be crucial in reaping the fullest benefits from such novel multimodal approaches.